Time in therapeutic range of tacrolimus in allogeneic hematopoietic stem cell transplant recipients is associated with acute graft-versus-host disease prophylaxis - Naoki Yoshikawa; Yukina Ehara; Yusei Yamada; Yuki Matsusaki; Kazuya Shimoda; Ryuji Ikeda (Scientific Reports)
Abstract Intra-patient variability in immunosuppressive blood drug concentrations is a potential biomarker in managing organ transplant patients. However, the association between the time in therapeutic range of tacrolimus blood concentrations and its efficacy in preventing graft-versus-host disease remains unknown. In this study, we analyzed the relationship between the time in therapeutic range of tacrolimus blood concentrations and its efficacy in acute graft-versus-host disease prophylaxis in patients undergoing allogeneic hematopoietic stem cell transplantation. Eligible patients administered tacrolimus were categorized into two groups based on the grade of acute graft-versus-host disease, and propensity score matching was performed using graft-versus-host disease prophylaxis protocols and days to the disease onset to compare time in therapeutic range. In patients with tacrolimus blood concentration therapeutic range ≥ 10 ng/mL, time in therapeutic range during the first 4 weeks post-transplantation was significantly lower in the Grade II–III than in the Grade 0–I group. Among propensity score matching-extracted patients, the Grade II–III group had significantly lower time in therapeutic range during the first 2 and 4 weeks post-transplantation. Our results suggest that high time in therapeutic range early post-transplantation, particularly within 4 weeks, may avert the severity of acute graft-versus-host disease.